2018
DOI: 10.1007/s00425-018-2890-1
|View full text |Cite
|
Sign up to set email alerts
|

A member of cation diffusion facilitator family, MTP11, is required for manganese tolerance and high fertility in rice

Abstract: Rice MTP11 is the trans-Golgi-localized transporter that is involved in Mn tolerance with MTP8.1, and it is required for normal fertility. Rice (Oryza sativa L.) is one of the most manganese (Mn)-tolerant species, and it is able to accumulate high levels of this metal in the leaves without showing toxic symptoms. The metal tolerance protein 8.1 (MTP8.1), a member of the Mn-cation diffusion facilitator (CDF) family, has been shown to play a central role in high Mn tolerance by sequestering Mn into vacuoles. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…Therefore, a secretory pathway involving vesicular trafficking and exocytosis mediated by AtMTP11 is believed to help increase Mn tolerance in Arabidopsis [28]. Similar functions of other MTPs in sequestering Mn into the Golgi apparatus have been reported for OsMTP11 from rice [27], HvMTP8.1 and HvMTP8.2 from barley [77], PtMTP11.1 and PtMTP11.2 from poplar ( Populus trichocarpa ) [28], as well as BmMTP10 and BmMTP11 from beets ( Beta vulgaris ) [78].…”
Section: Intracellular Mn Detoxification In Subcellular Compartmentsmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, a secretory pathway involving vesicular trafficking and exocytosis mediated by AtMTP11 is believed to help increase Mn tolerance in Arabidopsis [28]. Similar functions of other MTPs in sequestering Mn into the Golgi apparatus have been reported for OsMTP11 from rice [27], HvMTP8.1 and HvMTP8.2 from barley [77], PtMTP11.1 and PtMTP11.2 from poplar ( Populus trichocarpa ) [28], as well as BmMTP10 and BmMTP11 from beets ( Beta vulgaris ) [78].…”
Section: Intracellular Mn Detoxification In Subcellular Compartmentsmentioning
confidence: 92%
“…For example, activation of the antioxidant system, including the free radical-mitigating antioxidant enzymes and nonenzymatic components, is thought to be vital for plants alleviating excess Mn-induced oxidative stress [25]. The important roles of the regulation of Mn uptake, translocation, and distribution have been implicated in many plants’ responses to Mn toxicity, such as rice ( Oryza sativa ) [26,27], Arabidopsis ( Arabidopsis thaliana ) [28], and Caribbean stylo ( Stylosanthes hamata ) [29]. Furthermore, plants can sequester Mn into subcellular compartments, such as vacuoles, the endoplasmic reticulum (ER), Golgi apparatuses, and cell walls, to withstand the toxic effects of high Mn stress [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Both OsMTP8.1 and OsMTP8.2 were tonoplast-localized Mn transporters, and OsMTP9 was involved in efficient root Mn uptake (Chen et al, 2013; Ueno et al, 2015; Takemoto et al, 2017; Tsunemitsu et al, 2018b). Moreover, OsMTP11 played a crucial role in Mn tolerance through intracellular Mn compartmentalization, although the correct localization of this protein was still under debate (Farthing et al, 2017; Zhang and Liu, 2017; Ma et al, 2018; Tsunemitsu et al, 2018a). In addition, some MTP proteins from cucumber were recently isolated and their corresponding substrates were also specified.…”
Section: Introductionmentioning
confidence: 99%
“…For example, loss-of-function analyses of metal tolerance protein (MTP) demonstrate the importance of Mn sequestration into vacuoles in Mn tolerance in rice ( Oryza sativa ) and Arabidopsis [20, 21]. Recently, it has been shown that sequestration of Mn into Golgi-associated compartments by the function of OsMTP11 is also important for Mn homeostasis in rice [22]. Additionally, organic acids exuded from the root apex can chelate Mn, thereby alleviating Mn toxicity via decreasing Mn uptake by the roots [2325].…”
Section: Introductionmentioning
confidence: 99%